Досвід вивчення прискореного розмноження інтродукованих деревних рослин у Донецькому ботанічному саду НАН України - Довбиш, Н.Ф.; Шпакова, О.Г.; Малина, Н.Г.; Хархота, Л.В. (Промышленная ботаника, 2004)
A brief survey of investigations results of accelerated propagation of arboreal and coniferous plants introduced at the Donetsk Botanical Gardens of the National Academy of Sciences of Ukraine has been conducted. Achievements concerning studying of regenerative capacity of the introduced arboreal plants have been studied on the basis of their bioecologic peculiarities of growth and development. Perspectives of their mass propagation have been determined.